2018
DOI: 10.3389/fenvs.2018.00068
|View full text |Cite
|
Sign up to set email alerts
|

Pore-Scale Monitoring of the Effect of Microarchitecture on Fungal Growth in a Two-Dimensional Soil-Like Micromodel

Abstract: In spite of the very significant role that fungi are called to play in agricultural production and climate change over the next two decades, very little is known at this point about the parameters that control the spread of fungal hyphae in the pore space of soils. Monitoring of this process in 3 dimensions is not technically feasible at the moment. The use of transparent micromodels simulating the internal geometry of real soils affords an opportunity to approach the problem in 2 dimensions, provided it is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 47 publications
1
23
1
Order By: Relevance
“…Moreover, M. fragilis hyphae grown in TS show less variation in width and a more tortuous growth habit (as defined by deviation from straight lines of growth) than M. fragilis hyphae are grown without TS ( Figure 5C ). This suggests a possible influence of narrow pore space and touch stimuli offered by particles on fungal branching and morphology ( Soufan et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, M. fragilis hyphae grown in TS show less variation in width and a more tortuous growth habit (as defined by deviation from straight lines of growth) than M. fragilis hyphae are grown without TS ( Figure 5C ). This suggests a possible influence of narrow pore space and touch stimuli offered by particles on fungal branching and morphology ( Soufan et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The unique abilities of these systems to confine single cells and manipulate minute concentrations of liquids [27] make them ideal for simulating the microscale heterogeneity of soil systems [28]. Microfluidic chips have proven useful to study fungal hyphae [29][30][31], and can be applied to address a wide range of questions in soil ecology [32].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, for various reasons, and in particular the need in some experiments to use replicate soil columns, a number of authors have found it convenient to isolate uniformly sized aggregates from soils, and to repack them in a reproducible manner, prior to experiments to study a wide range of processes occurring within interaggregate pores (e.g., Juyal et al, 2019; Pot et al, 2015). As long as the repacked soil materials are not confused with the original soils, one could again consider that no real harm is done, as is the case also to some extent when one works with soil‐like micromodels (e.g., Soufan et al, 2018). Given the opportunity, it would always make more sense to work directly with undisturbed soil samples, in spite of their inherent heterogeneity, but as more reproducible alternatives, one has to acknowledge that repacked columns may occasionally be useful.…”
Section: Multiple Evidence Of Bypassmentioning
confidence: 99%